Pengaruh Kinerja Lingkungan, Good Corporate Governance Terhadap Nilai Perusahaan dengan Kinerja Keuangan Sebagai Variabel Intervening pada Perusahaan BUMN yang Terdaftar di BEI Periode 2021-2024 - Ambarwati, Salva Dewi; Rachmawati, Titiek (Economic Reviews Journal, 2025)
Using financial performance as an intervening variable, this study investigates how environmental performance and Good Corporate Governance (GCG) affect company value. Eight state-owned enterprises were selected purposively, and data was obtained from the Indonesia Stock Exchange and the companies' official websites. To conduct this analysis, descriptive statistics, validity and reliability tests, inner model evaluation, and hypothesis testing through bootstrapping were used. The results of the study indicate that sustainability and governance are not yet major considerations for the market, as environmental performance and GCG do not have a direct impact on company value. While GCG does not have a significant impact, environmental performance has been proven to improve financial performance. In addition, financial performance has the ability to control the influence of environmental performance on company value; however, it cannot control the relationship between GCG and company value. These findings confirm that financial performance is the most dominant factor in the formation of company value.